6500 BP Oldsquaw Duck (Clangula hyemalis) from Northern Ellesmere Island, Arctic Archipelago, Canada - Stewart, Thomas G.; Hourston-Wright, Jean (ARCTIC, 1990)
A nearly complete skeleton, including partially preserved feathers, of an Oldsquaw duck (Clangula hyemalis L.) was recovered from Holocene marine deposits in Clements Markham Inlet, Ellesmere Island, N.W.T., Canada. The specimen was 2 m lower in the section than allochthonous terrestrial plants previously dated at 6400 ± BP (Sl-4314) and is estimated to be 6500 years old. These deposits represent a marine, prodeltaic sedimentary environment that emerged from the fiord as the result of postglacial isostatic uplift. Comparison of the specimen's present elevation and age with the inlet's emergence curve indicates the duck was buried in a paleowater depth of 38 m. Isostatic uplift is ubiquitous in the Canadian Arctic, exposing ocean bottoms and prodeltas. The deposits from these environments deserve closer scrutiny for fossils by Quaternary scientists, as they can contribute to a better understanding of the biologic development of the Canadian Arctic.